Are coveralls required as personal protective equipment during the management of COVID-19 patients? - Jongtak Jung (BMC, 2021)
Abstract Objectives Few studies have investigated the contamination of personal protective equipment (PPE) during the management of patients with severe-to-critical coronavirus disease (COVID-19). This study aimed to determine the necessity of coveralls and foot covers for body protection during the management of COVID-19 patients. Methods PPE samples were collected from the coveralls of physicians exiting a room after the management of a patient with severe-to-critical COVID-19 within 14 days after the patient’s symptom onset. The surface of coveralls was categorized into coverall-only parts (frontal surface of the head, anterior neck, dorsal surface of the foot cover, and back and hip) and gown-covered parts (the anterior side of the forearm and the abdomen). Sampling of the high-contact surfaces in the patient’s environment was performed. We attempted to identify significant differences in contamination with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) between the coverall-only and gown-covered parts. Results A total of 105 swabs from PPEs and 28 swabs from patient rooms were collected. Of the PPE swabs, only three (2.8%) swabs from the gown-covered parts were contaminated with SARS-CoV-2. However, 23 of the 28 sites (82.1%) from patient rooms were contaminated. There was a significant difference in the contamination of PPE between the coverall-only and gown-covered parts (0.0 vs 10.0%, p = 0.022). Conclusions Coverall contamination rarely occurred while managing severe-to-critical COVID-19 patients housed in negative pressure rooms in the early stages of the illness. Long-sleeved gowns may be used in the management of COVID-19 patients.